Hospital Management System (HMS) - Diwyanjalee K.V.S; Widanapathirana W.P.V.K; Perera J.S; Warnakulasuriya I.S.G; De Silva D. I; Samarasekara H.M.P.P.K.H (International Journal of Engineering and Management Research, 2022)
A hospital management system (HMS) is a computer-based or web-based software that makes it easy to manage how well a hospital or other medical facility is performing. This system will help to make the entire function paperless. It integrates all information related to patients, doctors, appointments, hospital administrative details, etc. into one system. It has sections for the various professionals that make up the hospital. This study on hospital management systems is designed to transform the manual way of searching, sorting, storing, and accessing hospital information (files) into electronic medical records to solve related problems. This paper generally seeks a more accurate, reliable, and efficient computational method to facilitate hospital record keeping in hospitals and thus ensure an efficient result that reduces time consumption. Registering, and storing details in the system as well as computerized inventory, doctors, patients, and appointments. The interfaces are very user-friendly. Data processing is fast as it is highly secured for personal use. The initiative aims to automate every aspect of the hospital.